Penthetria Meigen (Diptera: Bibionidae): Revision of the New World species and world catalog - Fitzgerald, Scott J. (Zootaxa, 2021)
The New World species of Penthetria Meigen are revised. Eight species are recognized: P. appendicula Hardy, P. arizonensis Fitzgerald n. sp., P. distincta Hardy, P. dolichopeza Fitzgerald n. sp., P. heteroptera (Say), P. mexicana (Hardy), P. neonigrita Fitzgerald n. sp., and P. yakima Fitzgerald n. sp.. Penthetria heros Say and P. nigerrima (Bellardi) are considered unrecognized (nomen dubium) and P. nigrita Perty is transferred to the genus Plecia Wiedemann, where it is a junior synonym of Plecia plagiata Wiedemann. The fossil species Penthetria dubia Geinitz is removed from family Bibionidae. Additionally, a summary of current knowledge about the genus, a generic description and diagnosis, and a catalog of the 36 (extant) world species are provided.